Kepemimpinan Ketua Kelas dan Perannya terhadap Dinamika Sosial Mahasiswa di Lingkungan Kelas (Studi pada Mahasiswa Kelas MSDM-A Program Studi Manajemen Universitas Muhammadiyah Bandung) - Laila Nurbani Cahyadi; Naja Putri Rahmadhani; Nanda Putri Arizta; Nirina Hanifah Safanissa; Hani Humaeriyah (INDO PUBLISHING, 2026)
This study aims to analyze the leadership of a class leader in managing students’ social dynamics in MSDM-A Class, Management Study Program, Universitas Muhammadiyah Bandung. The class was formed by merging several classes with different backgrounds, resulting in differences of opinion, participation levels, and potential conflicts in class decision-making. This research employed a qualitative approach using interviews and observations involving five purposively selected students. The findings reveal that the class leader acts as a communication facilitator, conflict mediator, and liaison between lecturers and students. A predominantly democratic leadership style encourages student participation in deliberative processes, although not all students are actively involved. Supporting factors include open communication and social closeness, while inhibiting factors involve diverse student characteristics and limited participation among some members.